2005
DOI: 10.1037/0033-2909.131.5.684
|View full text |Cite
|
Sign up to set email alerts
|

Age-of-Acquisition Effects in Word and Picture Identification.

Abstract: Words and pictures with earlier learned labels are processed faster than words and pictures with later learned labels. This age-of-acquisition (AoA) effect has been extensively investigated in many different types of tasks. This article provides a review of these studies including picture naming, word naming, speeded word naming, word pronunciation durations, lexical decisions, eye fixation times, face recognition, and episodic memory tasks. The measurement and validity of AoA ratings is discussed, along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
269
1
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(302 citation statements)
references
References 183 publications
(540 reference statements)
18
269
1
14
Order By: Relevance
“…A third and increasingly compelling account has emerged from connectionist modeling of ageof-acquisition effects (e.g., Juhasz, 2005). Its logic is as follows: A memory network organizes itself, through larger weight changes, into a certain efficient configuration early on to represent what it knows about (e.g., a childhood language); it cannot nimbly reorganize itself even if the nature of the input changes (e.g., a second language).…”
Section: Discussionmentioning
confidence: 99%
“…A third and increasingly compelling account has emerged from connectionist modeling of ageof-acquisition effects (e.g., Juhasz, 2005). Its logic is as follows: A memory network organizes itself, through larger weight changes, into a certain efficient configuration early on to represent what it knows about (e.g., a childhood language); it cannot nimbly reorganize itself even if the nature of the input changes (e.g., a second language).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of AoA on word recognition and production has been demonstrated not only in adults, but also in preschool and/or school-aged children using a variety of different tasks (Assink, van Well, & Knuijt, 2003;Garlock, Walley, & Metsala, 2001;Johnson & Clark, 1988;Walley & Metsala, 1990, 1992. Despite the fact that robust effects of AoA have been reported in a variety of different populations and tasks, some researchers have dismissed this effect, suggesting that AoA is another measure of word frequency (Juhasz, 2005). Although some researchers have reported a moderately strong, negative correlation between AoA and word frequency, others have shown that the effects of AoA are much stronger than those of word frequency and they occur even when word frequency has been controlled (see Juhasz, 2005, for reviews).…”
Section: Age Of Acquisition Effectsmentioning
confidence: 99%
“…This source gained importance in research on the age-of-acquisition effect in visual word recognition, which demonstrates that words learned early in life keep a processing advantage over words learned later in life, even when corrected for the best possible frequency norms (for reviews, see Ghyselinck, Lewis, & Brysbaert, 2004;Johnston & Barry, 2006;Juhasz, 2005; see also Cortese & Khanna, 2007, for the most recent evidence on this for English monosyllabic words). The database most often used for childhood frequencies in English is the Zeno database (Zeno, Ivens, Millard, & Duvvuri, 1995).…”
Section: Edited Texts May Not Be the Best Source Of Information For Wmentioning
confidence: 99%